2019
DOI: 10.1016/j.arthro.2018.11.058
|View full text |Cite
|
Sign up to set email alerts
|

All-Arthroscopic Reconstruction of Severe Chronic Acromioclavicular Joint Dislocations

Abstract: Purpose: To report the outcomes of all-arthroscopic coracoclavicular (CC) ligament reconstruction and simultaneous diagnosis and treatment of glenohumeral pathologies in patients with symptomatic, chronic (>6 weeks), complete (Rockwood type III-V) acromioclavicular joint (ACJ) separations. Methods: We prospectively followed up 57 consecutive patients treated arthroscopically for chronic Rockwood type III (n ¼ 11), type IV (n ¼ 19), and type V (n ¼ 27) ACJ dislocations. Previous ACJ surgery failed in 11 (19%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Boileau et al 7 described an all-arthroscopic, modified WD procedure with double-button (EndoButton; Smith & Nephew Endoscopy) fixation for chronic type 3 to 5 AC joint dislocation and found a mean postoperative CMS of 85.5 and an overall redislocation rate of 11% after a mean follow-up of 36 months. Anatomic CC ligament arthroscopically assisted reconstruction has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Boileau et al 7 described an all-arthroscopic, modified WD procedure with double-button (EndoButton; Smith & Nephew Endoscopy) fixation for chronic type 3 to 5 AC joint dislocation and found a mean postoperative CMS of 85.5 and an overall redislocation rate of 11% after a mean follow-up of 36 months. Anatomic CC ligament arthroscopically assisted reconstruction has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The best surgical technique for AC joint dislocation is still in debate [ 5 ]. However, to our best knowledge, it is the first analysis of the triple tunnel with a double button at the clavicle in current literature.…”
Section: Discussionmentioning
confidence: 99%
“…When we look at outcomes previously reported with open procedures, shifting to arthroscopy does not appear to provide significant improvement. However, Lamplot et al, similar to Boileau et al, 15 reported that the percentage of associated lesions, mostly intra-articular, that were treated at the time of the ACJ procedure was 49%. In light of the reported results, should we really treat all the ACJ disruptions using an arthroscopic-assisted technique?…”
mentioning
confidence: 92%